2017
DOI: 10.1093/cvr/cvx181
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Th17 differentiation in Trim21 deficiency promotes a stable phenotype of atherosclerotic plaques with high collagen content

Abstract: In this study, we demonstrate that TRIM21 influences atherosclerosis via regulation of Th17 responses, with TRIM21 deficiency promoting IL-17 expression and a more fibrous, stable, phenotype of the plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 45 publications
5
43
0
1
Order By: Relevance
“…83 In COVID-19 patients, medium-to long-term CV consequences may be caused by increased IL-6 signalling. Experimental evidence supports an atherogenic role for IL-6 and CRS-related cytokines, 59,60,[84][85][86] as well as its effects on cardiac fibrosis and failure. 87 The cytokine increases adhesion molecule expression in human endothelial cells in vitro; 88 at the same time, stimulation of human macrophages with oxidized LDLs (oxLDLs) leads to increased release of IL-6.…”
Section: Covid-19 Inflammation and The Cytokine Release Stormmentioning
confidence: 85%
“…83 In COVID-19 patients, medium-to long-term CV consequences may be caused by increased IL-6 signalling. Experimental evidence supports an atherogenic role for IL-6 and CRS-related cytokines, 59,60,[84][85][86] as well as its effects on cardiac fibrosis and failure. 87 The cytokine increases adhesion molecule expression in human endothelial cells in vitro; 88 at the same time, stimulation of human macrophages with oxidized LDLs (oxLDLs) leads to increased release of IL-6.…”
Section: Covid-19 Inflammation and The Cytokine Release Stormmentioning
confidence: 85%
“…Interestingly, sterol metabolism has been observed to influence both immunoglobulin production and lymphocyte proliferation [47][48][49]. In addition, we have recently described an enhanced susceptibility to high-fat diet in Trim21 -/bone marrow-transferred Ldlr -/mice [19], with these mice developing significantly larger atherosclerotic plaques. This phenotype was linked to an increased differentiation and activation of the Th17 pathway in Trim21 -/mice, further emphasizing the link between altered sterol metabolism, the immune system and TRIM21.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously observed that naive, unmanipulated Trim21-deficient mice display no obvious phenotype. More recently, Trim21-deficient naive T cells have also been shown to have an augmented intrinsic capacity for T helper type 17 (Th17) differentiation [19]. More recently, Trim21-deficient naive T cells have also been shown to have an augmented intrinsic capacity for T helper type 17 (Th17) differentiation [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…us, we infer that Yixin Ningshen tablet may treat CHD primarily by regulating above 18 pathways, which awaits further validation. Of note, pathways with less than 10 target proteins, such as 17 cell differentiation (9) [95], VEGF signaling pathway (9) [96], Wnt signaling pathway (8) [97], folate biosynthesis (7) [98], tryptophan metabolism (6) [99], adipocytokine signaling pathway (6) [100], toll-like receptor signaling pathway (6) [101], choline metabolism (6) [102], platelet activation (5) [103], and linoleic acid metabolism (3) [104] were also validated to be closely related with CHD, which further proved the reliability of our target identification methods. e active compounds in Yixin Ningshen tablet regulate and restore the network equilibrium by targeting many proteins in many pathways, thereby mitigating the development of CHD.…”
Section: Enriched Pathways Of the Targetmentioning
confidence: 99%